2013
DOI: 10.1007/s00520-013-1782-y
|View full text |Cite
|
Sign up to set email alerts
|

Structured gastroenterological intervention and improved outcome for patients with chronic gastrointestinal symptoms following pelvic radiotherapy

Abstract: Gastroenterological evaluation identifies significant, potentially treatable diagnoses in patients who develop chronic GI symptoms following pelvic radiotherapy. Some findings are incidental and unrelated to previous cancer treatment. Radiation-induced GI symptoms have historically been considered "untreatable." We report the first data to show that structured gastroenterological assessment has the potential to improve outcome by identifying diagnoses and facilitating focused treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…In further cohort studies (23,29,30) and a randomized controlled trial (31), we showed that by asking patients to systematically define their symptoms, investigating them for each symptom using an algorithm and then treating all the identified abnormalities, patients improve. Our results have been corroborated by others (32) and suggest that specialist nurses can be trained to manage this patient group using our structured algorithmic approach. This is important since current gastroenterology services are unable to cope with the number of affected patients.…”
Section: Principle 3: the Physiological Model Of Gi Symptomatologysupporting
confidence: 87%
“…In further cohort studies (23,29,30) and a randomized controlled trial (31), we showed that by asking patients to systematically define their symptoms, investigating them for each symptom using an algorithm and then treating all the identified abnormalities, patients improve. Our results have been corroborated by others (32) and suggest that specialist nurses can be trained to manage this patient group using our structured algorithmic approach. This is important since current gastroenterology services are unable to cope with the number of affected patients.…”
Section: Principle 3: the Physiological Model Of Gi Symptomatologysupporting
confidence: 87%
“…This showed that if a clinician is systematic at eliciting which GI symptoms are present, then systematic in identifying the cause(s) for each symptom and then systematic in following an algorithm of treatment, patients with PRD can be helped significantly. This finding has been confirmed by others [10]. Another vital finding of the ORBIT trial, in an era when there are huge numbers of affected patients, is that a nurse can be trained to manage the patients following the algorithm and, with adequate gastroenterology support, can obtain outcomes similar to those obtained by a senior gastroenterologist in most cases.…”
supporting
confidence: 55%
“…The modified IBDQ was adopted to assess the primary outcome in HOT2, given its successful application in characterising patients with gastrointestinal dysfunction after pelvic radiotherapy. 6 , 8 , 11 , 15 , 16 , 17 None of the exploratory analyses using other instruments to measure rectal bleeding, including LENT SOMA, CTCAE, and EORTC, suggested any clinical benefit of hyperbaric oxygen.…”
Section: Discussionmentioning
confidence: 99%